Microbial transformations of natural antitumor agents: conversion of lapachol to dehydro-alpha-lapachone by Curvularia lunata. - Otten, S (1979)
Microbial transformation of lapachol, a naturally occurring naphthoquinone, was carried out by Curvularia lunata (NRRL 2178). The fungus brings about oxidative cyclization of the substrate to dehydro-alpha-lapachone, which was isolated and characterized by nuclear magnetic resonance and mass spectral analyses; its structure was verified by chemical synthesis. The metabolite is a naturally occurring chromene possessing antibacterial and antitumor activities.